Exchange rate Inflation and Unemployment in East European Economies: the Case of Poland and Hungary - Roberto Golinelli; Renzo Orsi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
The aim of this paper is to model the impact of exchange rate both inlation and unemployment variables in economics which are characterized by important structural changes, i.e. A transition phase moving from centralised economies towards market economies. This phenomeno, which is common to east european countries, stressed difefrent effects both for what concerns the behaviour of economic agents and for what concerns fiscal and monetary measures adopted by governments and aiming to keep under control the inflation-unemployment trade off. Time series relatioships between these variables are investigated within an econometric model. Economic theory and available data on the hypothetically relevant variables, along with the consideration of the main facts occured in the period under study, characterize our information set. It is found that single equation analysis yelds inefficient inference relative to the whole system analysis, and important structural changes are detected which reflect possible breaks in the structure of the economic system with a change in economic policy.
Keywords: 330